Quantification of aortic stiffness using MR Elastography and its comparison to MRI‐based pulse wave velocity. Issue 1 (15th November 2013) - Damughatla, Anirudh R.; Raterman, Brian; Sharkey‐Toppen, Travis; Jin, Ning; Simonetti, Orlando P.; White, Richard D.; Kolipaka, Arunark
<x xml:space="preserve">Abstract</x> Purpose To determine the correlation in abdominal aortic stiffness obtained using magnetic resonance elastography (MRE) (μMRE) and MRI‐based pulse wave velocity (PWV) shear stiffness (μPWV) estimates in normal volunteers of varying age, and also to determine the correlation between μMRE and μPWV. Materials and Methods In vivo aortic MRE and MRI were performed on 21 healthy volunteers with ages ranging from 18 to 65 years to obtain wave and velocity data along the long axis of the abdominal aorta. The MRE wave images were analyzed to obtain mean stiffness and the phase contrast images were analyzed to obtain PWV measurements and indirectly estimate stiffness values from the Moens‐Korteweg equation. Results Both μMRE and μPWV measurements increased with age, demonstrating linear correlations with R2 values of 0.81 and 0.67, respectively. Significant difference (P ≤ 0.001) in mean μMRE and μPWV between young and old healthy volunteers was also observed. Furthermore, a poor linear correlation of R2 value of 0.43 was determined between μMRE and μPWV in the initial pool of volunteers. Conclusion The results of this study indicate linear correlations between μMRE and μPWV with normal aging of the abdominal aorta. Significant differences in mean μMRE and μPWV between young and old healthy volunteers were observed. J. Magn. Reson. Imaging 2015;41:44–51. © 2013 Wiley Periodicals, Inc.